Актуальні проблеми забезпечення сировиною підприємств деревообробної промисловості в Україні - Guzhva, Igor; Ivanov, Yevhen (Dr. Viktor Koval, 2018)
Introduction. Woodworking industry splits into two main sectors – primary and deep processing of wood, which fundamentally differ from each other. While primary wood processing requires common timber assortments (usually coniferous) production of deep processing products – plywood, particleboards and fiberboards – needs valuable and scarce assortments of hardwood like alder or birch. Problems with access to valuable raw materials remain one of the key factors in the development of the Ukrainian woodworking industry for many years. Aim and tasks. The aim of the article is to identify main shortcomings of Ukrainian timber market that create the biggest obstacles for domestic deep wood processing business; and to propose legal and regulatory mechanisms for ensuring stable and priority access of woodworking enterprises to quality timber products. Research results. Woodworking industry development is constrained with smuggling of valuable hardwood assortments (birch and alder), which serve as raw material for the manufacture of veneer, plywood, fiberboard; as well as with large-scale exports of wood particles to Turkey. In addition, abolished State Forestry Agency’s Order #42 that obliged to distribute scarce hardwood assortments only among those businesses that have appropriate facilities for its rational consumption. This greatly enhanced risks to misuse rare wood varieties for the needs that can be met by consumption of less-quality or more widespread assortments. The results of economic modeling show that strengthening the negative tendencies with the access of domestic woodworking manufacturers to plywood raw materials will have a negative impact on all related industries, employment and the economy as a whole; Ukraine will increase raw material exports and imports of finished furniture and paper products produced from exported raw materials. Conclusions. In order to avoid a negative scenario in the deep wood processing industry, it is necessary to adopt the Law on the Timber Market built upon the principle of targeting access to technical and plywood raw materials. It’s also necessary to enact and guarantee the practical implementation on preserving Ukrainian forests and preventing the illegal export of unprocessed wood.